Diffuse alveolar hemorrhage following intravenous thrombolytic treatment in acute ischemic stroke: a case series - MİDİ, İPEK (SPRINGER-VERLAG ITALIA SRL, 2020)
Diffuse alveolar hemorrhage (DAH) following fibrinolytic therapy is a rare but a life-threatening complication. In acute ischemic stroke (AIS), DAH as a complication was not reported following intravenous thrombolytic therapy (ITT). The demographic, clinical, radiologic, and prognostic data of 4 patients with AIS who developed DAH after ITT are presented in this case series, along with a literature review.
Keywords: Diffuse alveolar hemorrhage; Intravenous thrombolytic treatment; Acute ischemic stroke; Prognosis; THERAPY